Algunos hongos hipogeos nuevos o poco citados de Cataluña (Zygomycotina, Ascomycotina y Basidiomycotina) - Vidal i Frigola, Josep Maria (Revista Catalana de Micologia, 2007)
Some new or rare hypogeous fungí frorn Catalonia (Spain) (Zygomycotina, Ascomycotina and Basidiomycotina): 54 species and 3 varieties of hypogeous fungi are reported. 25 of them are new to Catalonia (1 Zygomycete, 13 Ascomycetes and 11 Basidiomycetes), and 6 of them are new records in the Iberian Peninsule: Elaphomyces citrinus Vitt., E. Granulatus Fr. varo asperulus (Vitt.) Hawker, Genea vagans Mattir., Sphaerozone Ostiolatum (Tul. apud Berk. et Br.) Setch., Arcangeliella borziana Cavo and Gautieria Morchelliformis Vitt. var. globispora Pilát. Most of them have been described and illustrated by O.M. photographs, and new data about their ecology and phenology have been supplied. Some new synonims are proposed: Genea pulchra Corda with G. Hispídula Berk. et Br.; Gautieria otthii ss. Pilát with G. Graveolens Vitt.; G. Graveolens ss. Pilát with G. Morchelliformis var. globispora Pilát; G. Mexicana ss. auct. Eur. and G. Pallida ss. Soehner with G. Otthii Trog; Octavianina olida Malç. et Astier with Hydnangium aurantiacum Heim et Malç.; Hymenogaster Olivaceus Vitt. and H. sulcatus Hesse with H. citrinus Vitt.; H. arenarius Tul. et C. Tul., H. tenir Berk. et Br. and H. mutabilis Soehner with H. niveus Vitt.; H. muticus Berk. et Br. with H. populetorum Tul. et C. Tul. ; H. ludmilae Velen. with H. vulgaris Tul. apud Berk et Br.; Hysterangium thwaitesii Berk. et Br., H. siculum Mattir. and H. rickenii Soehner with H. clathroides Vitt. ; H. separabile ss. auct. Eur. non Zeller with H. coriaceum Hesse; Sclerogaster porquerollensis Donad. et Riouss. and S. Rhizopogon Donad. et Riouss. with Wakejieldia macrospora (Hawker) Hawker.